Complete Absence (Destruction) of Crowns of Teeth Indications for the Use of Pin Structures - Allabergenova Umida Mahsud Kizi; Madrakhimova Munisa Alisher Kisi; Dadaboeva Mukhlisa Ulugbekovna (Genius Journals, 2022)
The Purpose of the study to improve the quality of orthopedic treatment of patients with low and destroyed clinical crowns ofteeth by improving the designs ofthe stump pin inlay and artificial crown.
Keywords: crown; stump; designs; quality